Workshop report: The importance of indigenous voices in climate change policy (page 5) - Nyang'ori Ohenjo (2023)
This workshop provided a platform for indigenous peoples’ representatives to outline their priority needs to input into Third National Climate Change Action Plan (NCCAP, 2023-27) that is led by the Ministry of Environment and Forestry through the Climate Change Directorate. An accelerated programme of the finalisation has targeted the government launch of the NCCAP 2023-2027 at the Africa Climate Summit, in Kenya, in September 2023. The representatives of indigenous peoples, who included a representation of women, youth, and persons with disabilities, at the meeting for 3rd and 4th August 2023, discussed their experiences about environmental justice and its cross-cutting aspects within the 7 sectors. This discussion is geared towards generating data that will inform the development of the NCCAP 2023-27 and influence policy positions including the upcoming Africa Climate Summit, the UNFCCC processes and the national climate change policies and initiatives. This meeting provided opportunities for translating constitutional & policy gains in recognition of indigenous knowledge systems and practices related to climate change into meaningful programs and actions at the county and country levels.